ANALISIS PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA HANDPHONE NEXIAN - Pantri Heriyati; Septi Septi (Bina Nusantara University, 2012)
Nexian is a popular local brand mobile phone among Indonesian people. Nexian’s popularity may be caused by the increasing use of mobile internet and social media. Through Nexian mobile phone, user can browse internet, play music, watch TV, watch video, receive and send email, use facebook and twitter beside text message and call. The main object of this study is to analyze the influence of brand image and product quality on consumer purchasing decisions of Nexian mobile phone. Research was conducted on 110 respondents of Nexian mobile phone users who live in Jakarta. The results of this study stated that brand image have a significant influence on purchasing decisions. Meanwhile product quality only have a little impact on consumer purchasing decisions on Nexian mobile phone, which might be expected because consumers do not consider Nexian as a qualified mobile phone. Research Methodology that used to collect the data is survey questionnaire and multiple regression for analyze the data.